Clostridium difficile flagella predominantly activate TLR5-linked NF-κB pathway in epithelial cells. (April 2016) - Batah, Jameel; Denève-Larrazet, Cécile; Jolivot, Pierre-Alain; Kuehne, Sarah; Collignon, Anne; Marvaud, Jean-Christophe; Kansau, Imad
Abstract: Clostridium difficile has become the most common enteropathogen responsible for intestinal nosocomial post-antibiotic infections. This has coincided with the appearance of serious cases related to the emergence of hypervirulent strains. The toxins are the main virulence factors and elicit an inflammatory response during C. difficile infection. However, other bacterial components appear to be involved in the inflammatory process. In some pathogens, flagella play a role in pathogenesis through abnormal stimulation of the TLR5-mediated host immune response. To date, few studies have addressed this role for C. difficile flagella. In the current study, we confirm in two different epithelial cell models that C. difficile thanks to its FliC flagellin interacts with TLR5. In addition, thanks to inhibition and transcriptomic studies we demonstrate that the interaction of flagellin and TLR5 predominantly activates the NF-κB and, in a lesser degree, the MAPK pathways, via TLR5, leading to up-regulation of pro-inflammatory gene expression and synthesis of pro-inflammatory mediators. These results suggest a role for C. difficile flagella in contributing to inflammatory response in host intestinal cells. Highlights: We used two cell line models to characterize Clostridium difficile flagellin-TLR5 signaling. C. difficile flagellin predominantly activates the NF-κB signaling pathway. MAPKs signaling pathways are also activated by C. difficile flagellin, but to a lesser degree. Transcriptomic studies provide new data concerning the committed effectors and cytokines induced by FliC-TL5 interaction. C. difficile flagellin elicits up-regulation of pro-inflammatory gene expression and pro-inflammatory cytokine synthesis.